Kajian Filosofi Hukum Hindu Dalam Pustaka Manawadharmasastra - I Ketut Subagiasta; Ni Wayan Gateri (Satya Dharma : Jurnal Ilmu Hukum, 2022)
The study of efforts to understand Hindu religious law in the Manawadharmasastra sacred literature aims to discuss four points, namely the law of creation, the sources of Hindu law, the law of marriage, and the law of earning income. Further in Hindu law that the universe and its contents were created by God Almighty named Hyang Purusa who created the contents of this nature by creating the element of water and with God's power and omnipotence then made the drinya into two parts namely Purusa and Padhana. The method used in this paper is the library method.